Genetic identification of arsenate reductase and arsenite oxidase in redox transformations carried out by arsenic metabolising prokaryotes – A comprehensive review. (November 2016) - Kumari, Nisha; Jagadevan, Sheeja
Abstract: Arsenic (As) contamination in water is a cause of major concern to human population worldwide, especially in Bangladesh and West Bengal, India. Arsenite (As(III)) and arsenate (As(V)) are the two common forms in which arsenic exists in soil and groundwater, the former being more mobile and toxic. A large number of arsenic metabolising microorganisms play a crucial role in microbial transformation of arsenic between its different states, thus playing a key role in remediation of arsenic contaminated water. This review focuses on advances in biochemical, molecular and genomic developments in the field of arsenic metabolising bacteria – covering recent developments in the understanding of structure of arsenate reductase and arsenite oxidase enzymes, their gene and operon structures and their mechanism of action. The genetic and molecular studies of these microbes and their proteins may lead to evolution of successful strategies for effective implementation of bioremediation programs. Highlights: Genetic identification in arsenic metabolising bacteria has been reviewed. Understanding of the enzyme structure and their mechanism of action are discussed. Potential applications of these bacteria in bioremediation programs are proposed.